2001
DOI: 10.1152/jappl.2001.90.2.501
|View full text |Cite
|
Sign up to set email alerts
|

Training induces nonuniform increases in eNOS content along the coronary arterial tree

Abstract: Exercise training produces enhanced nitric oxide (NO)-dependent, endothelium-mediated vasodilator responses of porcine coronary arterioles but not conduit coronary arteries. The purpose of this study was to test the hypothesis that exercise training increases the amount of endothelial NO synthase (eNOS) in the coronary arterial microcirculation but not in the conduit coronary arteries. Miniature swine were either exercise trained or remained sedentary for 16--20 wk. Exercise-trained pigs exhibited increased sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
105
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 49 publications
9
105
1
1
Order By: Relevance
“…We also found that high volume intens exercise led to hypertension and impairment of endothelium-dependent vascular relaxation, with marked and diffuse increases in eNOS and iNOS across three aortic layers. It is well recognized that NO participates in exerciseinduced enhancement of vascular function and remodeling (13,14,(19)(20)(21). In the present study, we also found a significant increase in aortic eNOS content after acute and chronic endurance training, in accordance with increased acetylcholine-induced vascular relaxation.…”
Section: Discussionsupporting
confidence: 86%
“…We also found that high volume intens exercise led to hypertension and impairment of endothelium-dependent vascular relaxation, with marked and diffuse increases in eNOS and iNOS across three aortic layers. It is well recognized that NO participates in exerciseinduced enhancement of vascular function and remodeling (13,14,(19)(20)(21). In the present study, we also found a significant increase in aortic eNOS content after acute and chronic endurance training, in accordance with increased acetylcholine-induced vascular relaxation.…”
Section: Discussionsupporting
confidence: 86%
“…It may be possible that mechanisms and time course of vascular adaptations to deconditioning may differ between conduit (diameter) and resistance vessels (hyperemic flow response), as has been indicated previously in exercise-training studies in animals 26,27 and humans. 28 This hypothesis, however, needs further investigation.…”
Section: Baseline and Hyperemic Vascular Characteristicsmentioning
confidence: 84%
“…For example, it is conceivable that different arteries possess distinct degrees of NO dependency. Previous studies have typically examined brachial or radial artery responses, making it somewhat difficult to extrapolate these findings to other conduit arteries, especially given the heterogeneity in endothelial NO synthase expression level 64 and vasodilator responsiveness 65 between different arterial beds. That said, the only extant femoral artery study demonstrated a significant effect of L-NMMA on the FMD response.…”
Section: Discussionmentioning
confidence: 99%